2014
DOI: 10.1016/j.yjmcc.2013.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II induces Fat1 expression/activation and vascular smooth muscle cell migration via Nox1-dependent reactive oxygen species generation

Abstract: Fat1 is an atypical cadherin that controls vascular smooth muscle cell (VSMC) proliferation and migration. Nicotinamide adenine dinucleotide phosphate (NADPH) oxidase 1 (Nox1) is an important source of reactive oxygen species (ROS) in VSMCs. Angiotensin II (Ang II) induces the expression and/or activation of both Fat1 and Nox1 proteins. This study tested the hypothesis that Ang II-induced Fat1 activation and VSMC migration are mediated by Nox1-dependent ROS generation and redox signaling. Studies were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 36 publications
1
52
0
Order By: Relevance
“…Case 1 contained a mutation in the tumor suppressor FAT1 atypical cadherin gene, which has been implicated in glioblastoma, colorectal adenocarcinoma, and head and neck squamous cell carcinoma [15]. While FAT1 is best known for promoting Wnt signaling, FAT1 expression has also been associated with ERK activation [21]. Therefore, mutations in HRAS , SND1 , and FAT1 may constitute separate genetic drivers that underlie the common MAPK activation observed in each SCO.…”
Section: Discussionmentioning
confidence: 99%
“…Case 1 contained a mutation in the tumor suppressor FAT1 atypical cadherin gene, which has been implicated in glioblastoma, colorectal adenocarcinoma, and head and neck squamous cell carcinoma [15]. While FAT1 is best known for promoting Wnt signaling, FAT1 expression has also been associated with ERK activation [21]. Therefore, mutations in HRAS , SND1 , and FAT1 may constitute separate genetic drivers that underlie the common MAPK activation observed in each SCO.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, accumulating evidences have demonstrated that MAPK may be involved in VSMCs migration [1417]. Zhan et al have revealed that dominant-negative mutants of MAPK, including JNK, ERK, and p38, significantly decreased PDGF-BB–induced VSMC migration [17].…”
Section: Discussionmentioning
confidence: 99%
“…VSMC primary cells were used in determining ROS and O2 − generation with dihydroethidium (DHE, Invitrogen, California), which oxidizes in the presence of ROS, generating fluorescence (Bruder-Nascimento et al , 2014; Silva et al , 2015). VSMCs were grown to confluence, and then seeded to 6-well plates.…”
Section: Methodsmentioning
confidence: 99%